Use of a commercial PCR kit for detecting Chlamydia trachomatis. Issue 9 (September 1993) - Smith, I W; Morrison, C L; Patrizio, C; McMillan, A
Abstract : AIMS--To evaluate a commercial polymerase chain reaction (PCR) kit for the detection of Chlamydia trachomatis. METHODS--Two hundred and fifty seven genital specimens, which had been submitted in 2SP medium for chlamydial isolation and subsequently stored at -70 degrees C, were retrospectively examined by a commercial PCR kit which detects chlamydial plasmid DNA. Culture negative, PCR positive specimens were examined by immunofluorescence and an in-house major outer membrane protein (MOMP)-PCR. RESULTS--All 49 specimens which were culture positive were also PCR positive. Another 14 specimens were also PCR positive. After resolution of these results by immunofluorescence and a PCR assay for MOMP the sensitivity for PCR was 98.4% and that of culture 79%. The specificities were 99.5% and 100%, respectively. CONCLUSIONS--This kit, which is highly sensitive and specific, is straightforward to use and has a built-in safeguard against cross contamination. The role of this test in the examination of routine genital specimens from patients with uncomplicated chlamydial infection is questionable due to its expense. It may have a place in the investigation of trachoma or infertility, however, where it has been shown that DNA can be detected when culture is unsuccessful.